Loyalitas guru ditinjau dari lingkungan kerja, pemberdayaan guru, kompensasi, dan kepemimpinan kepala sekolah pada SDIT Mutiara Insan Sukoharjo - Sigid Budi Raharjo; Sudarwati; Istiatin (ITB AAS Indonesia Surakarta, 2025)
The research objectives are to examine and analyze the influence of work environment on teacher loyalty at SDIT Mutiara Insan Sukoharjo. To examine and analyze the influence of teacher empowerment on teacher loyalty at SDIT Mutiara Insan Sukoharjo. To examine and analyze the influence of compensation on teacher loyalty at SDIT Mutiara Insan Sukoharjo. To examine and analyze the influence of principal leadership on teacher loyalty at SDIT Mutiara Insan Sukoharjo. This research type is descriptive quantitative. The research location is at SDIT Mutiara Insan Sukoharjo. The sample in this study consisted of 61 teachers. The sampling technique used was census technique, which means that the entire population was used as the research sample. Data analysis techniques included multiple linear regression analysis, t-test, F test, and coefficient of determination. Work Environment influences Teacher Loyalty at Integrated Islamic Elementary School Mutiara Insan Sukoharjo. Teacher Empowerment influences Teacher Loyalty at Integrated Islamic Elementary School Mutiara Insan Sukoharjo. Compensation influences Teacher Loyalty at Integrated Islamic Elementary School Mutiara Insan Sukoharjo. Leadership influences Teacher Loyalty at Integrated Islamic Elementary School Mutiara Insan Sukoharjo. Keywords: Teacher Loyalty, Work Environment, Teacher Empowerment, Compensation, Principal Leadership